The Effect of Teachers' Level of Self-Regulated Learning and Internet Self-Efficacy on Teaching Innovation in the Constructivist Curriculum - Budhi Santosa, Eka; Sukmawati, Fatma; Juwita, Ratna; Prihatin, Relly; Tri Cahyono, Budi; Suparmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
In the era of modern education, innovation in teaching is a crucial aspect for improving learning quality. This study aims to find out the extent to which Internet Self-Efficacy (ISE) of teachers affects learning innovation in the constructivist curriculum and the extent to which Self-Regulated Learning (SRL) affects teachers in making learning innovations in the constructivist curriculum. The research method used is quantitative with a survey approach. Data was collected through a questionnaire filled out by 97 junior high school teachers in Central Java who implemented a constructivist curriculum. Based on the results of the regression analysis, it was found that in the condition that teachers have a high level of Internet self-efficacy, self-regulated learning (SRL) has a significant effect on the learning innovations that are carried out by teachers. Another condition is the influence of SRL with low teacher ISE on teacher learning innovation. In the condition of low self-efficacy levels, SRL indicators of metacognitive skills, time management, and environmental settings did not have a significant effect on teachers' learning innovation. These findings indicate that teachers with high levels of self-regulated learning (SRL) and internet self-efficacy tend to be more innovative in implementing teaching methods that are in accordance with the principles of constructivism. The implications of this study emphasize the importance of developing teachers' self-regulated learning (SRL) and internet self-efficacy skills through continuous training and professional development programs to improve the quality of teaching in constructivist curricula.